1991
DOI: 10.1182/blood.v77.7.1593.1593
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation for high-grade lymphoid malignancy using melphalan/irradiation conditioning without marrow purging or cryopreservation. The Northern Regional Bone Marrow Transplant Group

Abstract: We report the safety and efficacy of 34 consecutive autologous bone marrow transplant (ABMT) procedures performed in adult patients with high-grade lymphoid malignancy after remission induction therapy. Fifteen patients with acute lymphoblastic leukemia (ALL) and six with high-grade non-Hodgkin's lymphoma (NHL) received pretransplant conditioning with intravenous (IV) melphalan and fractionated total body irradiation (TBI). Thirteen other patients with NHL were conditioned with melphalan alone, having previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Efforts to make the benefits of hematopoietic stem cell transplants acquaintable to a larger number of patients have been manifold [5-6, 9-11, 19]. Grafting PBSC instead of bone marrow stem cells has been shown to be less costly [20]; on the other hand we [4,5] and others [21][22][23][24][25] have shown that autografts can be performed safely without freezing devices, keeping the stem cells in a conventional blood bank refrigerator, at 4°C, for up to 96 hr. It has also been shown that stem cells can be frozen without controlled cryopreservation [26], that hematopoiesis can be restored using mobilized whole unprocessed blood [27], and that a single, large volume apheresis procedure could be enough to obtain apheresis products capable to reconstitute hematopoiesis after ablative chemotherapy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to make the benefits of hematopoietic stem cell transplants acquaintable to a larger number of patients have been manifold [5-6, 9-11, 19]. Grafting PBSC instead of bone marrow stem cells has been shown to be less costly [20]; on the other hand we [4,5] and others [21][22][23][24][25] have shown that autografts can be performed safely without freezing devices, keeping the stem cells in a conventional blood bank refrigerator, at 4°C, for up to 96 hr. It has also been shown that stem cells can be frozen without controlled cryopreservation [26], that hematopoiesis can be restored using mobilized whole unprocessed blood [27], and that a single, large volume apheresis procedure could be enough to obtain apheresis products capable to reconstitute hematopoiesis after ablative chemotherapy [26].…”
Section: Discussionmentioning
confidence: 99%
“…C onventional methods of cryopreservation of hematopoietic stem cells (HSCs) obtained from marrow or peripheral blood involve controlled-rate freezing using 10% dimethyl sulfoxide (DMSO) as the cryoprotectant and storage of the cells in liquid nitrogen. [1][2][3][4][5][6] Although the 10% DMSO method is cumbersome and requires complex equipment, it began to be used clinically for both autologous [7][8][9][10][11] and later allogeneic 12 human transplantation. Thus, cryopreservation using only DMSO has become standard involving 10% final concentration, controlled-rate freezing, and subsequent storage in liquid nitrogen.…”
mentioning
confidence: 99%
“…These autologous transplantation techniques were reported to yield early engraftment and reduced hospital length of stay, with significant cost savings. Outcomes were comparable to those from conventional conditioning with cryopreserved stem cells in patients with multiple myeloma [31][32][33][34]. Two recent studies of noncryopreserved autografts from developing countries using post-HSCT G-CSF also indicate comparable engraftment rates to cryopreserved autografts [35,36].…”
Section: Performing Autologous Hsct Without Stem Cell Cryopreservationmentioning
confidence: 75%
“…Several centers have recently reported outcomes of autologous HSCT for multiple myeloma using noncryopreserved stem cells without G-CSF support [31][32][33][34]. The success of this technique depends on abbreviated conditioning, with 1 day of high-dose melphalan for patients with multiple myeloma and short-duration conditioning for patients with lymphoma.…”
Section: Performing Autologous Hsct Without Stem Cell Cryopreservationmentioning
confidence: 99%